Paguristes karenae Craig & Felder 2022, n. sp. - Craig, Catherine W.; Felder, Darryl L. (Zenodo, 2022)
Paguristes karenae n. sp. (Figs 5B, 6–8) Paguristes tortugae. — Provenzano, 1959: 389, 392 (part, green carapace with red spines on cheliped carpus and manus inner margins), fig. 11A; Williams, 1965: 115, 119 (part, green carapace with red spines on cheliped carpus and manus inner margins, not fig. 96); McLaughlin & Provenzano, 1974 (part, “darker forms”); Williams, 1984: 205, fig. 144 (USNM 151492); Wicksten, 2005: 34, table 1 (part, uncertain identification suggested, footnote 20); Venera-Pontón et al ., 2020, 4, table 1 (part, ULLZ 13663, 13665, 13707, 13708). Paguristes sp. — Strasser & Price, 1999: 34, 41. Paguristes nr. tortugae .— Craig & Felder, 2021: table 1, 307, 311, 316, 317. Paguristes “nr. tortugae nov. sp. ”.— Craig & Felder, 2021: fig. 1, 312 Type material. Holotype : male DNA and photo voucher, sl 5.6 mm (ULLZ 4782 / USNM 1540546), Florida Keys, Pigeon Key, Florida, 09 June 2001, coll. K. Strasser (Barkel). Paratypes : Florida Atlantic coast and Keys: 1 female photo voucher, sl 3.2 mm (ULLZ 5647 / USNM 1542520), off Ft. Pierce, Florida, 15m, 09 Sep 2003; 1 male photo voucher, sl 6.1 mm, 1 male, sl 3.4 mm (ULLZ 12171 / USNM 1546239), Big Pine Key, Boogie Canal, scallop dredge, 2–3 m, 07 Jul, 1979; 1 male photo voucher, sl 6.3 mm (ULLZ 15244 / USNM 1548287) Content Keys, dredge, 2–4 m, 27 Jun 1984; 1 male photo voucher, sl 5.6 mm, 1 male, sl 4.3 mm (ULLZ 15245 / USNM 1548289), Big Pine Key, Newfoundland Harbor, dredge, 2–4 m, 25 Jun 1984; 1 male DNA voucher, sl 5.9 mm (UF 015380), Tampa Bay, 4 km West of Sunshine Skyway, spoil heap with sponges, 6–7 m, 07 Feb 2009. Northeastern Gulf of Mexico : 2 males, DNA and photo vouchers, sl 3.9, 4.9 mm (ULLZ 8578 / USNM 1543769), cruise NSF-III-055, 28°10.28’N, 84°1.95’W, 41 m, 04 Jul 2006. Belize . 1 female DNA and photo voucher, sl 3.0 mm, 1 female sl 2.0 mm (ULLZ 11116 / USNM 1545590), Twin Cays, rubble, 20 Feb 2009; 1 male photo voucher, sl 4.2 mm (ULLZ 3563 / USNM 1540063), Carrie Bow Cay, 1 m, 20 Apr 1983. Panama (Caribbean) : 1 ov ...